Accuracy of Transcutaneous Bilirubin Versus Serum Bilirubin Measurement in Preterm Infants Receiving Phototherapy: A Systematic Review. (December 2020) - Hynes, Sharon; Moore, Zena; Patton, Declan; O'Connor, Tom; Nugent, Linda
Abstract : Background: Jaundice is a common condition among preterm infants in the neonatal intensive care unit (NICU). Total serum bilirubin (TSB) offers a gold standard tool for measurement, but blood sampling can be costly, time-consuming, and not without risks of infection and pain. Transcutaneous bilimeter (TcB) allows for noninvasive assessment of bilirubin. However, due to questions of accuracy the use of the TcB in preterm infants receiving phototherapy has not been widely adapted in the NICU. Purpose: To systematically review studies that measure TcB versus TSB bilirubin in preterm infants who are receiving phototherapy. Methods: A systematic electronic search of databases (CINAHL, EMBASE, Cochrane, Medline, PubMed) was completed for English language publications. No date limitation was placed on the search. Inclusion criteria were based on preterm infants that were in the NICU receiving or had recently received phototherapy. Results: Nine studies of different quantitative study designs were reviewed. A good to strong correlation between TcB and TSB in preterm infants receiving phototherapy was demonstrated. There was a stronger correlation found in studies that examined TcB in unexposed skin areas during phototherapy. Implications for Practice: TcB may allow for a reduction in blood sampling, which would reduce painful procedures, reduce the risk of infection and anemia resulting from repeated blood sampling. It also acts as a more time and cost-efficient measurement tool. Implications for Research: Larger scaled quantitative studies on the accuracy of TcB in preterm infants receiving phototherapy are needed to provide more evidence-based data and guide clinical practice on this topic. Abstract : Supplemental Digital Content is Available in the Text.